2016
DOI: 10.31018/jans.v8i3.1000
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of top-down factors with relation to ecological attributes of an endangered species Commiphora wightii

Abstract: Present study was aimed to explore the influence of top down factors on ecological attributes of Commiphora wightii collected from seven districts of arid and semi arid parts of the Rajasthan. Ecological variables in respect of 46 accessions of this species were quantified. To assess the explanatory factors governing quantified ecological variables, soil samples were collected to analyze soil texture, soil EC, pH, available potassium, available phosphorus and total soil nitrogen. Results showed that there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…1 Details of height, canopy and RIV (Table 1) revealed that it is a sub-dominant species (RIV=8.71 to 49.0). Similar dominance analysis in respect of another endangered species of Indian desert, Commiphora wightii, also revealed its sub-dominant status and this sub-dominant status was also related to soil potassium (Kulloli et al, 2016). It was recommended that for conservation of C. wightii, a mixed plantation with associated species would be more successful.…”
Section: Ecological Distributionmentioning
confidence: 71%
“…1 Details of height, canopy and RIV (Table 1) revealed that it is a sub-dominant species (RIV=8.71 to 49.0). Similar dominance analysis in respect of another endangered species of Indian desert, Commiphora wightii, also revealed its sub-dominant status and this sub-dominant status was also related to soil potassium (Kulloli et al, 2016). It was recommended that for conservation of C. wightii, a mixed plantation with associated species would be more successful.…”
Section: Ecological Distributionmentioning
confidence: 71%